MARKETING STRATEGY OF THE UNIVERSITY: FORMATION AND ITS EFFECTIVENESS EVALUATION REALIZATION - Natalia К. Shemetova (Образование и наука)
The study is aimed at developing an algorithm of formation of university’s marketing strategy and the development of evaluating methods of its effectiveness realization. Despite the competitive expansion of the educational services market and the transition to a system of university self-financing, researchers have not paid due attention to the process of developing the marketing strategy of the university and the evaluation of its effectiveness yet. Methods. The applied methods include the method of general systems theory, and the complex of specialized marketing tools (PEST-, SNWand SWOT-analysis). Results. The algorithm of university’s marketing strategy formation and methodology for its effectiveness assessing is given in five fields: economic, informational, social, integration, and demand stage. The set of criteria is worked out for every field listed above. The author has developed a formula for determining the total indicator or general index of the effectiveness of university’s marketing strategy. Scientific novelty. The prospects of using the algorithm of formation of university’s marketing strategy and the system of monitoring and evaluating the effectiveness of marketing in higher vocational education was proved and evaluated by the author in the Ural Institute of Management of RANEPA. Practical significance. The research results can be used by the experts in the field of management of the higher educational institutions, and also as teaching materials while preparing the experts in marketing.